HUMAN PERFORMANCE MODELS AND HUMAN ERRORS IN AIR TRAFFIC MANAGEMENT - Kharchenko, Volodymyr P.; Chynchenko, Yuriy V. (Proceedings of National Aviation University (archive), 2008)
The models of air traffic controller performance and principles of estimation and prevention of errors in the course of controller professional activity are considered.